Factors influencing crop rotation strategies on organic farms with different time periods since conversion to organic production. Issue 1 (2nd January 2017) - Chongtham, Iman Raj; Bergkvist, Göran; Watson, Christine A.; Sandström, Emil; Bengtsson, Jan; Öborn, Ingrid
Abstract: Productive crop rotations are central to the success of organic production systems. The selection and sequence of crops are determined by a combination of agronomic and economic factors as well as the principles and standards of organic farming. Semi-structured interviews were conducted with sixteen organic farmers in Central-east Sweden to explore the factors that influence the design of crop rotations and the trade-offs between these factors, taking into account the length of time since conversion to organic production. We discerned three crop rotation strategies: strict, flexible and liberal, based on how crop(s) are repeated over time. A major trade-off for arable farmers was between perennial leys to provide nitrogen and control weeds, and the use of more inputs such as purchased nutrients and mechanical weed control to allow continuous cereal production. Critical considerations for livestock farmers were the length of ley for feed production and weed control, cost of re-seeding leys and decisions about whether to grow crops to feed animals or cereals to sell. Farmers practicing organic for a long time (more than 10 years) often had flexible rotations to adapt to changing conditions, but they generally included leys and a selection of annual crops in line with the principles of crop rotation and organic farming. Recently converted organic farmers usually concentrated on controlling weeds and producing sufficient livestock feed by following strict crop rotations. We conclude that farm type and experience strongly influenced rotation strategies and that weed management and market prices were the most important influences.